A Cadaveric Investigation of the Dorsal Scapular Nerve. (15th August 2016) - Nguyen, Vuvi H.; Liu, Hao (Howe); Rosales, Armando; Reeves, Rustin
Abstract : Compression of the dorsal scapular nerve (DSN) is associated with pain in the upper extremity and back. Even though entrapment of the DSN within the middle scalene muscle is typically the primary cause of pain, it is still easily missed during diagnosis. The purpose of this study was to document the DSN's anatomy and measure the oblique course it takes with regard to the middle scalene muscle. From 20 embalmed adult cadavers, 23 DSNs were documented regarding the nerve's spinal root origin, anatomical route, and muscular innervations. A transverse plane through the laryngeal prominence was established to measure the distance of the DSN from this plane as it enters, crosses, and exits the middle scalene muscle. Approximately 70% of the DSNs originated from C5, with 74% piercing the middle scalene muscle. About 48% of the DSNs supplied the levator scapulae muscle only and 52% innervated both the levator scapulae and rhomboid muscles. The average distances from a transverse plane at the laryngeal prominence where the DSN entered, crossed, and exited the middle scalene muscle were 1.50 cm, 1.79 cm, and 2.08 cm, respectively. Our goal is to help improve clinicians' ability to locate the site of DSN entrapment so that appropriate management can be implemented.